The Role of the Museum Space Narrative in Constructing Historical Memory - A. I. Voronina (Концепт: философия, религия, культура, 2021)
The paper concerns the issue of representation of historical memory. The museum is analyzed as the particular site of emergement of such a representation. The circulation of specific narratives belonging to a museum is viewed as the research object that is able to provide insights into the construction of historical memory. Therefore, the purpose of the undertaken study is to identify the role of the museum narrative in the formation of memory. This article focuses on the ways of exposing and assessing the effect that museum exhibitions and the concepts and the meaning they translate to the audience have on memory creation. The approach of the interdisciplinary scholar field of memory studies provides a framework for such an analysis. In particular, since the spatial dimension of memory is concerned, the contributions of Hayden White and of the theory of realms of memory of Pierre Nora are crucial. The text deconstructs the memory formation processes taking place in the space of museums using these theoretical and methodological ideas. The paper meets methodological challenges and research questions with conducting a case study. The exhibition of the Museum of the Mologa District that is a part of the Rybinsk State Historical, Architectural and Art Museum Preserve at the Russian Yaroslavl Region serve as the source of oral, textual and visual narratives. This museum offers a view on local history that is in a way unusual for Russian museums — it provides a less formal perspective, and, in addition, the museum was founded by an initiative group of the displaced people from the submerged town of Mologa. The museum displays are dedicated to this town that disappeared because of the construction of the Rybinsk hydroelectric power plant. With limited material evidence to illustrate the Mologa life, this role is passed to oral histories and memory narratives. Thus, based on the historical memory literature, the paper considers that the museum described could be characterized as a memory museum, different from traditional historical museums because of emotional links in the presentation of past events. The author concludes that the image of the flooded city presented in the museum is directly related to the traumatic nature of the social memory of the settlers. Thus, the meanings and the significance of the museum overflow to the realms of memory.